Peningkatan Motivasi dan Aktivitas belajar IPA Melalui Pendekatan Saintifik pada siswa kelas IV SDN Ende 1 - Adi Neneng Abdullah; Yuliani Sepe Wangge (Jayapangus Press, 2021)
This study aims to improve motivation and science learning outcomes through a scientific approach at SDN Ende 1, Ende Utara District, Ende Regency. This research is a classroom action research. The subjects in this study were students of grade IV, amounting to 30 people. The procedure in this study consisted of four stages, namely the planning stage, the implementation stage, the observation stage and the reflection stage. Data were collected through observation techniques and questionnaires. Data were analyzed by means of descriptive qualitative and descriptive quantitative. The results showed that the motivation and learning activities of science through the scientific approach had increased. In the first cycle there were 17 students whose learning motivation was in good and very good criteria with a percentage of 56.7%. And in cycle II learning motivation increased to 86.7%, where there were 26 students who were in good and very good criteria. Learning activities also increased, namely 65.71 in cycle I increased to 79.04 in cycle II with a good category